(untitled) (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Pujiastuti Y, Arsi, Sandi S. 2020. Characteristics of Bacillus thuringiensis isolates indigenous soil of South Sumatra (Indonesia) and their pathogenicity against oil palm pests Oryctes rhinoceros (Coleoptera: Scarabaeidae). Biodiversitas 21: 1287-1294. Bacillus thuringiensis is a gram-positive, entomopathogenic bacterium that could be isolated from soil and be used to control various plant pests. Oryctes rhinoceros is an important pest in oil palm. Application of B. thuringiensis-based bioinsecticides is an alternative in controlling these pests. The purposes of this study were to isolate and identify B. thuringiensis bacteria from the soil of South Sumatra, production of B. thuringiensis-based bioinsecticides and to test their toxicity to O. rhinoceros larvae. The study was conducted in several cities/districts in the province of South Sumatra. Soil samples were taken from various habitats and B. thuringiensis isolates were grown on NGKG agar media. Among 76 soil samples (6 districts and 2 cities) B. thuringiensis colonies were obtained leading to 24 isolates of B. thuringiensis. Toxicity screening tests for armyworm Spodoptera litura were 55.79% (53 isolates) and their mortality to 25.26% O. rhinoceros larvae (24 isolates). From these isolates whose effectively killed O. rhinoceros larvae, 10 isolates were taken and propagated with Nutrient Broth (NB) and biourine enriched with 5% molasses. Number of spores produced was counted during 24, 48 and 72 hours. Furthermore, a bioassay test was carried out on O. rhinoceros larvae for 7 days. Isolate of KJ3P1 caused the highest mortality of O. rhinoceros larvae after 7 days of observation. SDS Page resulted in KJ3P1 and KJ3R5 isolates showing several bands whose content of various types of protein molecular weight. Isolation of B. thuringiensis in South Sumatra produced 2 isolates potentially to be active ingredients in production of bioinsecticides which were effective in killing O. rhinoceros larvae.